Usulan Penerapan Contractor Safety Management System Pada Tahap Pra Kualifikasi di PT. UES Menggunakan Gap Analysis - Yulizan Rizki; Rani Aulia Imran; Katon Muhammad; Harun Indra Kusuma; Ahmad Faisal Ridho (Universitas Islam Raden Rahmat, Malang, 2024)
PT. UES, a construction service company, is preparing to participate in the prequalification stage of the Contractor Safety Management System (CSMS) for project tenders. This research aims to measure the implementation of CSMS during the prequalification stage using the gap analysis method. This method compares data sets to identify gaps. The research methodology includes distributing questionnaires to relevant respondents and reviewing the company's safety documents. The results show a compliance percentage of 73%, indicating gaps between the company's CSMS implementation and the standards set by the employer, thus necessitating improvements in the company's CSMS implementation